O ato alimentar em três espécies de Artibeus de grande porte (Chiroptera: Phyllostomidae) do Sudeste brasileiro - Ulian, Carina Maria Vela [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
The alimentary act of three species of frugivorous bats of the genus Artibeus: A. lituratus, A. fimbriatus and A. planirostris, in a total of nine individuals, was studied by observations in field and captivity, during the months of May to September of 2008. With the objective to caracterize the form of consumption of two tipes of fruits (soft and consistent) and it relates with the dentary structure of this bats, the alimentary act was film and analysed later. It had little variation between the species. The fruits had been consumed in similar way, being that statistics analisis had demonstrated that consistent fruits had received more lateral bytes than the soft fruits. The dentary analisis shown that the posterior teeth (pre-molar and molar) present important characteristcs to triturate pieces of more consistent fruits and the incisors serve to scrape the pulp of the soft fruits. This study it served to describe the form of feeding of frugivorous bats, that little is explained in the studies of alimentary behavior

Foi estudado o ato alimentar de três espécies de morcegos frugívoros do gênero Artibeus: A. lituratus, A. fimbriatus e A. planirostris, em um total de nove indivíduos, por meio de observações de campo e em cativeiro, durante os meses de maio a setembro de 2008. Com o objetivo de caracterizar a forma do consumo de dois tipos de frutos (macio e consistente) e relacioná-la a estrutura dentária desses morcegos, o ato alimentar foi filmado e analisado posteriormente. Houve pouca variação entre as espécies. Os frutos foram consumidos de maneira semelhante, sendo que análises estatísticas demonstraram que frutos consistentes receberam mais mordidas laterais que os frutos macios. A análise dentária mostrou que os dentes posteriores (pré-molares e molares) apresentam características importantes para triturar os pedaços de frutos mais consistentes e os incisivos servem para raspar a polpa de frutos macios. Esse estudo serviu para descrever a forma de alimentação de morcegos frugívoros, que é pouco explicada nos estudos de comportamento alimentar
Keywords: Morcego; Sementes - Disseminação